The gig economy in the UK: a regional perspective. Issue 3 (15th August 2019) - Johnes, Geraint
Abstract : Purpose: A quarterly series of gig economy activity in the regions of the UK is constructed. Patterns of regional linkages are identified and the implications of spatial patterns for policymakers, businesses, workers and institutions are highlighted. Design/methodology/approach: The Labour Force Survey data on main job self-employment in key gig economy sectors are used to construct the series. These are then analysed using vector autoregression techniques to identify patterns in the data and provide provisional forecasts. Findings: The incidence of gig economy activity is greatest in the London region, characterised by high population density and a concentration of service sectors in which gig economy work, particularly of a highly skilled nature, takes place. Growth of gig economy activity in other regions has been more modest. In London, the percentage of workers in the gig economy is expected to rise to around 6.5 per cent over the next few years, while in other regions, the percentage is expected to settle at between 3 and 4.5 per cent. Originality/value: These are the first regional estimates to be provided of the extent of gig economy activity. This is important in the context of discussions about the future of work, not least because regional disparities imply the need for policies addressing insecurity to have a spatial dimension.